PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. KALIMAS KHARISMA BANJARBARU - Mursidi Mursidi; Anthonius Junianto Karsudjono (Al-Kalam Jurnal Komunikasi, Manajemen dan Bisnis, 2023)
Aims to determine the influence of the work environment and work motivation onemployee performance at PT Kalimas Kharisma Banjarbaru. This study uses the method ofMultiple Linear Regression Analysis. Respondents involved in this study were employees ofPT Kalimas Kharisma Banjarbaru. The method used in this study is Multiple LinearRegression Analysis to determine the effect of each variable Work Environment, WorkMotivation, on Employee Performance at PT. Kalimas Kharisma Banjarbaru. By taking asample of 57 people and processing the data using the SPSS application program. Theresults showed that the work environment and work motivation had a significant partialeffect on employee performance at PT Kalimas Kharisma Banjarbaru. While simultaneouslyall the variables of the Work Environment, Work Motivation affect Employee Performanceat PT. Kalimas Kharisma Banjarbaru